2016
DOI: 10.1103/physrevb.94.045305
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic transverse drift of long current-induced spin coherence in two-dimensional electron gases

Abstract: We imaged the transport of current-induced spin coherence in a two-dimensional electron gas confined in a triple quantum well. Nonlocal Kerr rotation measurements, based on the optical resonant amplification of the electrically-induced polarization, revealed a large spatial variation of the electron g factor and the efficient generation of a current-controlled spin-orbit field in a macroscopic Hall bar device. We observed coherence times in the nanoseconds range transported beyond half-millimeter distances in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
5
12
0
Order By: Relevance
“…The peak with lower frequency corresponds to the lower density in the third subband, and the other two correspond to similar densities in the first and second subband. The first two subbands are almost degenerate (∆ 12 ∼ 0) as confirmed by calculation [31]. We found that ∆ 12 is very sensitive to the width of the lateral wells (increasing rapidly for smaller widths).…”
Section: Magnetoresistance In Perpendicular Magnetic Fieldssupporting
confidence: 80%
See 4 more Smart Citations
“…The peak with lower frequency corresponds to the lower density in the third subband, and the other two correspond to similar densities in the first and second subband. The first two subbands are almost degenerate (∆ 12 ∼ 0) as confirmed by calculation [31]. We found that ∆ 12 is very sensitive to the width of the lateral wells (increasing rapidly for smaller widths).…”
Section: Magnetoresistance In Perpendicular Magnetic Fieldssupporting
confidence: 80%
“…the band gap energy, the Kerr rotation extrema occur in the opposite direction. A similar observation of Kerr rotation extrema occurring on either side of the band gap has been reported in TRKR study of similar multilayer system [31]. The signal at λ = 819 nm included two exponential decay and was fitted to a bi-exponential decay function.…”
Section: Spin Dynamics In Sample Bsupporting
confidence: 72%
See 3 more Smart Citations